Penglibatan remaja dalam jenayah curi motosikal di Kuala Lumpur - Abdul Majid, Abdul Aziz; Abdullah, Nawi; Boerhannoeddin, Ali (The Malaysian Journal of Social Administration, 2017)
The aim of this study is to analyse motorcycle theft among teenagers in Kuala Lumpur. Thirty-three teenagers who were involved in motorcycle theft during police investigation had been interviewed. Majority of them acknowledged that they were influenced by their peer group. The crimes were committed together with a group of friends with similar background. This study also shows that 80.0% of the teenagers arrested Jiff motorcycle theft were between the ages of 15-18 .years old, while the remainder were between the ages of 12-14 years old. Indeed, the incidence of motorcycle theft among teenagers in Kuala Lumpurfrom 2003 to 2007 is on the increase. All related social institutions such as Community Surveillance Group, Non-Governmental Organizations, and even security and educational organ4ations need to act in a coherent and concerted manner to battle this crime. Pa. ilure to act swiftly will allow this ’small crime" to threaten the existing social harmony.